THE POLITICAL CULTURE THE PATRONAGE SYSTEM AND THE RELATIONSHIP NETWORK IN THE DEVELOPMENT OF LOCAL POLITICS - Purimart, Paiwan (Journal of MCU Nakhondhat, 2023)
The objectives of this research article are: 1) Study the political culture of the patronage system in Nakhon Ratchasima Province. 2) Study the network of relationships in the development of local politics in Nakhon Ratchasima Province. 3) Present the model of the political culture of the patronage system and the network of relationships in development. local politics Using qualitative research methods. Important informants include local politicians Local government officials political science academic community leader representatives Public sector representatives total 18 people. Data analysis was done by describing the information. The results of the research found that: 1) The political culture of the patronage system in Nakhon Ratchasima Province. The foster care system changes from a one-to-one relationship to a relationship of mutual assistance. Go in and build relationships to happen. By means of helping and strengthening the patronizing relationship with the leaders. To give help sacrifice dare to think, dare to act dare to make decisions have vision support various activities and merit making events in the area. 2) Network of relationships in the development of local politics in Nakhon Ratchasima Province. Network of relationships among friends and associates social relationships that are characterized by mutual dependence and assistance. Help and support with sincerity. When there is an election at the local level relatives allies and friends they will help and support each other strongly. 3)Political culture model, patronage system and relationship network in local political development. Having faith in the principles of democratic governance Adhere and believe in the importance and dignity of the person. Respect the rules of democratic governance Participate in political and administrative activities Have a sense of their civic duty and have confidence in themselves. Optimism has trust in fellow human beings. Know how to criticize with reason and in a constructive way. and not having a dictatorial mind.